An exploration of workarounds and their perceived impact on antibiotic stewardship in the adult medical wards of a referral hospital in Malawi: a qualitative study - Chimwemwe Tusekile Mula; Nicola Human; Lyn Middleton (BMC, 2019)
Abstract Background Antibiotic stewardship, the proper management of antibiotics to ensure optimal patient outcomes, is based on quality improvement. Evidence-based guidelines and protocols have been developed to improve this process of care. Safe and timely patient care also requires optimal coordination of staff, resources, equipment, schedules and tasks. However, healthcare workers encounter barriers when implementing these standards and engage in workarounds to overcome these barriers. Workarounds bypass or temporarily 'fix' perceived workflow hindrances to achieve a goal more readily. This study examines workaround behaviours that nurses and doctors employ to address the challenges encountered during their antibiotic stewardship efforts and their impact, at a tertiary hospital in Malawi. Methods This was a qualitative descriptive case study design and is part of a large mixed methods study aimed at understanding nurses' role in antibiotic stewardship and identifying barriers that informed the development of nurse-focused interventions. For this study, we conducted interviews with staff and observations of nurses antibiotic stewardship practices on two adult medical wards. We convened three focus group discussions with doctors, pharmacists and laboratory technologists (n = 20), focusing on their attitudes and experiences with nurses' roles in antibiotic stewardship. We also observed nurses' antibiotic stewardship practices and interactions duringfour events: shift change handovers (n = 10); antibiotic preparation (n = 13); antibiotic administration (n = 49 cases); and ward rounds (n = 7). After that, the researcher conducted follow up interviews with purposively selected observed nurses (n = 13). Results Using inductive and deductive approaches to thematic analysis, we found that nurses established their ways of overcoming challenges to achieve the intended task goals with workarounds. We also found that nurses' practices influenced doctors' workarounds. We identified six themes related to workarounds and grouped them into two categories: "Taking shortcuts by altering a procedure" and "Using unauthorized processes". These behaviors may have both positive and negative impacts on patient care and the health care system. Conclusion The study provided insight into how nurses and doctors work around workflow blocks encountered during patient antibiotic management at a tertiary hospital in Malawi. We identified two categories of workaround namely taking shortcuts by altering a procedure and using unauthorized processes. Addressing the blocks in the system by providing adequate resources, training, improving multidisciplinary teamwork and supportive supervision can minimize workarounds.